Covid-19 Policy at the Village level: Analysis of PTC-19 in Handling Covid-19 in Panggungharjo Village: English - Yogar, Bagaskoro Nur Abu; Sakir; Prasetyo, Satria Iman (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2022)
The background of this study is the covid-19 virus outbreak which has an impact on the health sector in the Special Region of Yogyakarta (DIY). The problem urges the Panggungharjo Village Government to innovate public services, especially digital-based public services to minimize physical contact. Answering these problems, the Panggungharjo Village Government made Panggungharjo Covid-19 Response (PTC-19). Through PTC-19, it is expected to suppress the growth rate of the COVID-19 virus outbreak in the local area. The research method uses a qualitative type with a case study approach. The data in this study were obtained through in-depth interviews, as well as literature studies taken through a number of previous studies. The data obtained were analyzed using Qualitative Data Analysis Software with a cross tab feature in NVivo 12 Pro. In addition, the data analyzed also using interactive model techniques through three aspects of analysis, including: data reduction, data presentation, and drawing conclusions. The purpose of this study is to determine the public policy cycle in PTC-19. Researchers use William Dunn's public policy cycle theory which has three indicators, 1) Agenda Formulating, 2) Policy Formulation (Policy Implementation), 3) Policy Legitimacy (Monitoring and Evaluation). This theory makes it easier for researchers to identify the problems behind the creation of PTC-19, available facilities, and monitoring and evaluation of PTC-19. Keywords: PTC-19, Covid-19, Panggungharjo